1991
DOI: 10.1007/bf02049926
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of handsewn over stapled bowel anastomosis

Abstract: Bowel anastomoses are conventionally performed using a handsewn technique or a stapling device. Each has potential benefits and disadvantages. The most clinically significant complications of the bowel anastomosis are anastomotic leakage and stricture formation. The indices of healing and tissue cohesion were compared dynamically over time in 24 dogs randomized to undergo either a standard two-layer handsewn anastomosis or a stapled anastomosis with the Premium CEEA (United States Surgical Corporation, Norwalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 22 publications
2
42
1
Order By: Relevance
“…98,99 However, one of these had significantly more patients with corticosteroids in the stapled group, 99 while the other included 505 hand-sewn compared with 28 stapled colorectal anastomoses in 20 years. 98 Thirteen experimental studies 41,45,50,[90][91][92][93][94][95][96][97]105,106 included herein found results approximately similar to those in the clinical setting: no significant differences in AL, with equal or higher ABP in stapled colorectal anastomosis.…”
Section: Hand-sewn Vs Stapled Colorectal Anastomosissupporting
confidence: 49%
“…98,99 However, one of these had significantly more patients with corticosteroids in the stapled group, 99 while the other included 505 hand-sewn compared with 28 stapled colorectal anastomoses in 20 years. 98 Thirteen experimental studies 41,45,50,[90][91][92][93][94][95][96][97]105,106 included herein found results approximately similar to those in the clinical setting: no significant differences in AL, with equal or higher ABP in stapled colorectal anastomosis.…”
Section: Hand-sewn Vs Stapled Colorectal Anastomosissupporting
confidence: 49%
“…This was considered to be due to the fact that the surgeon used a standardized suture technique and the quality of the surgery he performed remained the same. Furthermore, hand-suture anastomoses show better tissue alignment than those made with automatic suturing devices which use standard diameters and compression levels [5]. The measured values for leaks and ruptures correspond with the results of available animal studies on dogs, pigs, and horses [2,4,7,8].…”
Section: Discussionmentioning
confidence: 63%
“…However, improper handling of the stapler may lead to a partial tear of the anastomosis and leakage (17,18), whereas irregular suturing of the mucosa may lead to hyperplasia, granulation tissue and scar formation, which may cause a stricture (19,20). Furthermore, there was no reported difference in the morbidity and mortality rates between the hand-sewn and stapled techniques (21,22). Additionally, stapling has been criticized as it confers an increase in the overall expediture and, Single-layer continuous suture contributes to the reduction of surgical complications in digestive tract anastomosis involving special anatomical locations in certain cases, such as preoperative obstruction of the digestive tract, mucosal edema, increased thickness of the muscle layer and healing dysfunction, the use of staplers is restricted.…”
Section: Introductionmentioning
confidence: 99%